Dukungan Sosial dan Stigma HIV/AIDS pada Pekerja: Sebuah Tinjauan Sistematis - Wulandari, Ayu; Mubarokah, Kismi (Griya Widya: Journal of Sexual and Reproductive Health, 2024)
Background: HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immuno Deficiency Syndrome) are global problems that every year new cases are increasing. HIV cases Indonesia is the 5th country at risk of HIV and AIDS in Asia. The purpose of this study was to determine the social support and stigma of HIV/AIDS in workers. Method: The method used is Systematic Review (SR) using PubMed and ProQuest databases. The search strategy used PICO (general workers as a population, social support as an intervention, the results of social support and HIV/AIDS stigma on workers). The selected journal articles are in English, published in 20211-2021, and general workers. The results of data extraction are three journal articles reviewed from various countries such as South Africa and Tanzania Result: The results of the journal articles that have been reviewed show that the social support provided is acceptable for the stigma felt by workers. With the existence of social support can help provide assistance in the form of care, affection and positive support for people infected with HIV AIDS and to improve the quality of life of people infected with HIV / AIDS. Recommendation: Based on this research, the workplace provides support for dealing with HIV/AIDS in the workplace and provides social and health support for employees infected with HIV/AIDS and for workers to provide support, motivation and encouragement if there are other workers who are HIV positive. For the public to always look for correct and reliable information related to HIV/AIDS